The Impartation of the Gifts of the Spirit in Paul’s Theology - Ervin Budiselić (Kairos (English Ed.))
This article analyzes an idea that the gifts of the Spirit can be imparted from one person to another person based on Romans 1:11 and 1Timothy 4:14. The author’s thesis is that such a theology is unbiblical because it does not recognize the distinction between the gifts of the Spirit and spiritual gifts, and claims that the gifts of the Spirit can be imparted from one person to another. Also, the doctrine and practice of impartation violates the Reformation’s teaching about the priesthood of all believers because believers are encouraged to rely on people and not on God in order to receive something from God. In this way, particularly gifted individuals in the church are no longer intercessors or vessels which God uses to work in the lives of other people, but they are elevated to the position of mediators which actually reflects the Roman Catholic doctrine about saints and priests as mediators between God and people.